Reconstructing the mass accretion histories of nearby red nuggets with their globular cluster systems. Issue Volume 15:Issue S359(2020) (March 2019) - Beasley, Michael A.; Leaman, Ryan; Trujillo, Ignacio; Montes, Mireia; Vazdekis, Alejandro; Rusiñol, Núria Salvador; Eftekhari, Elham; Ferré-Mateu, Anna; Martn-Navarro, Ignacio
Abstract: It is generally recognized that massive galaxies form through a combination of in-situ collapse and ex-situ accretion. The in-situ component forms early, where gas collapse and compaction leads to the formation of massive compact systems (blue and red "nuggets") seen at z > 1. The subsequent accretion of satellites brings in ex-situ material, growing these nuggets in size and mass to appear as the massive early-type galaxies (ETGs) we see locally. Due to stochasticity in the accretion process, in a few rare cases a red nugget will evolve to the present day having undergone little ex-situ mass accretion. The resulting massive, compact and ancient objects have been termed "relic galaxies". Detailed stellar population and kinematic analyses are required to characterise these systems. However, an additional crucial aspect lies in determining the fraction of ex-situ mass they have accreted since their formation. Globular cluster systems can be used to constrain this fraction, since the oldest and most metal-poor globular clusters in massive galaxies are primarily an accreted, ex-situ population. Models for the formation of relic galaxies and their globular cluster systems suggest that, due to their early compaction and limited accretion of dark-matter dominated satellites, relic galaxies should have characteristically low dark-matter mass fractions compared to ETGs of the same stellar mass.